Developing Professional Competencies in Medicine: Application of the Triple Jump Model in Problem-Based Learning in Medical Education - zohreh sadat alavi; sara heydari (Journal of Medical Education and Development, 2025)
This study explores developments in medical education with a focus on Problem-Based Learning (PBL) and the Triple Jump Model. PBL emerged as an innovative paradigm at McMaster University, replacing traditional teaching methods by promoting active, student-centered learning. The Triple Jump Model, integrating components of self-directed learning, problem-solving, and structured feedback, provides a framework for comprehensive assessment of professional competencies. Research indicates that combining these two approaches can significantly enhance medical students' cognitive and professional skills. Findings demonstrate the efficacy of this integrated model in facilitating the transfer of theoretical knowledge to clinical practice."